Sending a message to the top: the influence of service delivery protests on service delivery planning in South African municipalities - John Mamokhere (Insights into Regional Development)
South Africa has seen a surge in service delivery protests in recent years. These protests are often due to the inadequate provision of services. Unemployment, poor housing, water and sanitation, electricity, corruption and municipal administration, health, and crime have all been cited as causes of the protests, which have been termed a "poor's rebellion". Given the service dissatisfaction, residents often use protest as a means of communication to influence policy and decision-making. However, this study sought to assess the influence of service delivery protests on service delivery planning using Bolobedu South under the jurisdiction of Greater Tzaneen Municipality. The study utilised a qualitative research approach to collect and analyse the primary results. The citizens residing at Greater Tzaneen Municipality have been interviewed using a face-to-face semi-structured interview guide and the data was analysed using thematic content analysis. The finding of this study shows that service delivery protests are a common phenomenon in South Africa, with citizens protesting over the inadequate delivery of basic services such as shelter, electricity, water and sanitation. Service delivery protests are legally recognised in South Africa. However, as much as they are legally recognized, they are often disruptive and undermine the maturity of democracy. The study recommends that it is essential to engage with the community regularly and ensure that they are aware of the municipality's plans and progress. This engagement should be ongoing and not just when protests erupt. When people feel that they are being heard and that their concerns are being addressed, they are less likely to resort to protests. It also recommends improved communication and engagement between the municipality and the communities they serve. This can involve regular meetings, consultations, and feedback mechanisms that allow community members to express their concerns and provide input on service delivery planning (IDP).